(untitled) (Research, Society and Development, 2020)
This study investigates the effect of different compositions of high-grain diets on lamb termination on performance and changes in ingestive and physiological behavior. Twenty-four male lambs were used, with no defined racial pattern, with an average initial weight of 20.9 kg, at 6 months of age. Three diets containing different proportions of concentrate and roughage (100:0, 80:20, and 60:40) were supplied, with the concentrated portion of the diets being composed 85% whole-grain corn and 15% commercial pelletized supplement. There was no effect (P > 0.05) of the test diets for the consumption of dry matter (MS), mineral matter (MM), neutral detergent fiber (FDN), total carbohydrates (CT) and total digestible nutrients (NDT), expressed in g/day and % of live weight. The averages of total and daily weight gain and slaughter weight were similar (P > 0.05) between diets, registering daily weight gain of 0.302, 0.254 and 0.259 g/day with 100, 80 and 60% of concentrated, respectively. Lambs fed exclusively with concentrate decreased the time dedicated to rumination (P ≤ 0.05), and showed greater efficiency in feeding (EAL) and rumination (ERU). The animals in the diet without roughage showed marked variation in temperature in the rumen region, while lambs from the diets with 80 and 60% concentrate showed changes in temperatures close to the same evaluation period. All evaluated diets showed satisfactory performance, and despite the changes observed in the animals ingestive behavior, these were not sufficient to impair the lambs performance indices.